PELAKSANAAN PEMBEBASAN BERSYARAT TERHADAP NARAPIDANA (STUDI KASUS DI LEMBAGA PEMASYARAKATAN NARKOTIKA KELAS IIA JAKARTA PERIODE 1 JANUARI 2023 S/D 31 DESEMBER 2023) - Ihza, Fahrurrozi; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
Pembebasan Bersyarat is a process of developing convicts outside prison to integrate with family and society. Pembebasan Bersyarat for prisoners is a form of policy in the correctional system that gives prisoners the opportunity to leave prison and serve part of their sentence outside. This research will discuss the Conditional Release Arrangements for Prisoners and Obstacles in Implementing Conditional Release for Prisoners (Case Study at the Lembaga Pemasyarakatan Narkotika Kelas IIA Jakarta for the Period 1 January 2023 to 31 December 2023) The legal research method used is the normative juridical legal research method which supported by empirical data. Using a statutory approach obtained from primary, secondary and tertiary legal material sources. Conditional Release Arrangements for Prisoners are regulated in Article 10 letter (f) in Law Number 22 of 2022 concerning Corrections and Conditional Release Arrangements for Narcotics Crime Convicts, namely Article 87 in Minister of Law and Human Rights Regulation Number 7 of 2022 concerning Second Amendment to Regulations Minister of Law and Human Rights Number 3 of 2018 concerning Conditions and Procedures for Granting Remission, Assimilation, Leave to Visit Family, Conditional Release, Leave Before Release, and Conditional Leave. And in the future it will be regulated in Article 72 of Law Number 1 of 2023 concerning the Criminal Code. Obstacles in Implementing Conditional Release for Prisoners (Case Study at the Lembaga Pemasyarakatan Narkotika Kelas IIA Jakarta for the Period 1 January 2023 to 31 December 2023) namely Strict Rules or Regulations, Lack of Family Support, Negative Views of the Community, Potential to Commit Crimes and Limitations of Officers in Supervision.